Komparatif Kinerja Dosen yang Bersertifikasi Pada Universitas Swasta di Seberang Ulu Kota Palembang - Nisa' Ulul Mafra; Tri Sinarti (MBIA, 2019)
This study aims to compare and find out whether there are differences in the perfomance of certified lecturers at private universities in Seberang Ulu, Palembang. The population in this study were 325 respondents. The sample used by Slovin calculation is 76 respondents, with random sampling analysis technique. The analysis model used is the Analysis of Variance (ANOVA) test. The result obtained after testing revealed that there was a significant difference in the perfomance of certified lecturers at these private universities.